Perceived Benefit, User Satisfaction And Ease of Use of Mobile Augmented Reality (MAR) Shopping Aid - Hanafi, Hafizul Fahri; Samsudin, Khairulanuar; Said, Che Soh; Zalay, Abdul Aziz (International Business Education Journal, 2015)
This aim of this study is to examine the effectiveness of mobile shopping aid using mobile devices through augmented reality. Against the background of emerging trends in mobile shopping, the researchers offer a mobile shopping aid or tool developed on the web, technology that is heightened with a novel setting, namely the augmented reality technology. Essentially, augmented reality is a computing environment in which the real world (as experienced through the camera of a mobile phone in real time) is superposed with a synthetic user interface. To elicit opinions and feedback from potential users, a survey involving 60 students (20 boys and 40 girls) were recruited to collect data pertaining to three important measures, namely ease of use, perceived benefit, and user satisfaction. The data gathered were analysed, and the findings indicated that these three elements were significant in making online shopping more effective. Thus, these findings emphasize that these three factors have to be carefully factored in the design of such a novel mobile tool to help ensure shoppers become highly engaged and satisfied in online shopping.